Legal Studies Related To The Vina Murder Case In Realizing A Just Law - Yasin, Mohamad Hikmah; Suryadi, Slamet; Adriansyah, Rifky; Yusup Permana, Deni; Dikrurahman, Diky (Ann Publisher, 2024)
This journal discusses the case of Vina's murder in Cirebon, which has been in the public spotlight because of its heartbreaking tragedy and demands for justice. This study uses a juridical-normative method with a case study approach to analyze the legal remedies in handling the case. The data used consisted of primary data, such as laws and regulations and court documents, and secondary data in legal literature and related articles. The analysis is carried out qualitatively with descriptive-analytical techniques, evaluating the effectiveness and fairness of the legal process applied and the protection of the rights of victims and witnesses. The study results show that there are irregularities in the investigation, including a lack of transparency and professionalism of law enforcement officials, which can damage public trust in the legal system. The journal recommends increased transparency in the investigation process and fair law enforcement to ensure justice for victims and suspects. The conclusion emphasizes the importance of objective and professional application of the law in every stage of the criminal justice process to achieve true justice.